1995
DOI: 10.1113/jphysiol.1995.sp020571
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of sodium channels in short‐ and long‐term denervated rodent skeletal muscles.

Abstract: 1. Loose-patch voltage-clamp recordings were made from rat and mouse skeletal muscle fibres denervated for up to 6 weeks. Innervated muscles possessed a Na+ current density of 107 + 3-3 mA cm-2 in endplate membrane, and 6'3 + 0-6 mA cm-2 in extrajunctional membrane. This high concentration of Na+ channels at the endplate was gradually reduced following denervation. After 6 weeks of denervation, the endplate Na+ channel concentration was reduced by 40-50 %, and the density of Na+ channels in extrajunctional mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…To examine the role of Na v 1.5 expression in the hyperpolarized shift of sodium current inactivation we measured fast inactivation in 23 SD fibres in the absence and presence of 300 n m TTX. We confirmed that 300 n m TTX blocked nearly all sodium current carried by Na v 1.4 (Lupa et al 1995) in six control fibres (data not shown). In each SD muscle we recorded from several fibres in the absence of TTX and then recorded from the same series of fibres in the presence of TTX (see methods).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…To examine the role of Na v 1.5 expression in the hyperpolarized shift of sodium current inactivation we measured fast inactivation in 23 SD fibres in the absence and presence of 300 n m TTX. We confirmed that 300 n m TTX blocked nearly all sodium current carried by Na v 1.4 (Lupa et al 1995) in six control fibres (data not shown). In each SD muscle we recorded from several fibres in the absence of TTX and then recorded from the same series of fibres in the presence of TTX (see methods).…”
Section: Resultssupporting
confidence: 74%
“…To help identify fibres we stained endplates by applying 5 μg ml −1 rhodamine‐conjugated bungarotoxin (Molecular Probes, Eugene OR, USA) for 30 s. Sodium currents were recorded near (within 100–200 μm), but never over muscle fibre endplates. By assuming a K d of 1.9 μ m for Na v 1.5 (White et al 1991) and 5 n m for Na v 1.4 (Trimmer et al 1989; for review see Goldin, 2001) one can estimate that 300 n m TTX blocked 97% of Na v 1.4 and 23% of Na v 1.5 (Lupa et al 1995). We then solved for the percentage of Na v 1.4 and Na v 1.5 using the following equations: where Na tot is the amplitude of the sodium current before application of TTX and Na TTX is the sodium current after application of 300 n m TTX.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, both types of NaCh had the ability to become aggregated at the neuromuscular synapse. This conclusion was also supported by previous studies showing that the NaCh concentration persists at neuromuscular junctions after many weeks of denervation, and both TTX-sensitive and TTX-insensitive NaChs were concentrated at the denervated endplate (Caldwell and Milton, 1988;Lupa et al, 1995).…”
Section: Local Regulation Of Nach Expressionsupporting
confidence: 84%
“…Individual fibers of the rat extensor digitorum longus muscle were imaged in vitro as described above to allow placement of the patch and sharp electrodes on an individual fiber between 50 and 200 μm from an endplate (Fig 1A). All loose patch recordings were made >50 μM from the endplate to avoid the steep gradient of sodium channels that is present near the endplate22, 23 and persists following denervation 24. Prior to seal formation, the muscle was briefly impaled approximately 50 μm from the loose patch pipette with a sharp electrode (resistance greater than 20 MΩ) containing 3 M KCl and 10 ng/ml sulforhodamine to measure the resting potential of the fiber.…”
Section: Methodsmentioning
confidence: 99%